(untitled) (JS (JURNAL SEKOLAH), 2025)
Abstract: Poster media is a form of visual communication that is effective in conveying information in a concise, compact and attractive manner. This research evaluates the effectiveness of posters as a means of conveying information through literature studies from various fields, such as education, health, and marketing. Posters have been shown to improve learners’ understanding of complex material, be an effective educational tool in public health campaigns, and support marketing strategies by presenting strong and memorable visualizations. Key factors that influence the effectiveness of posters include design elements such as layout, typography, colors and images, as well as strategic placement locations. However, challenges in the digital age arise from competition with more dynamic interactive media, such as videos and social media platforms. This research uses a descriptive-qualitative approach to analyze relevant literature, providing recommendations for poster designs that are creative, communicative, and adaptive to modern audiences. The findings show that posters remain relevant in the digital age, provided they are strategically designed to enhance visual appeal and message effectiveness. This study contributes to a broader understanding of posters as a medium of information delivery across fields. Keyword: visual communication, poster media, information delivery Abstrak: Media poster adalah salah satu bentuk komunikasi visual yang efektif dalam menyampaikan informasi secara ringkas, padat, dan menarik. Penelitian ini mengevaluasi keefektifan poster sebagai sarana penyampaian informasi melalui studi literatur dari berbagai bidang, seperti pendidikan, kesehatan, dan pemasaran. Poster terbukti mampu meningkatkan pemahaman peserta didik terhadap materi kompleks, menjadi alat edukasi yang efektif dalam kampanye kesehatan masyarakat, serta mendukung strategi pemasaran dengan menghadirkan visualisasi yang kuat dan mudah diingat. Faktor utama yang memengaruhi efektivitas poster meliputi elemen desain seperti tata letak, tipografi, warna, dan gambar, serta lokasi penempatan yang strategis. Namun, tantangan di era digital muncul dari persaingan dengan media interaktif yang lebih dinamis, seperti video dan platform media sosial. Penelitian ini menggunakan pendekatan deskriptif-kualitatif untuk menganalisis literatur yang relevan, memberikan rekomendasi desain poster yang kreatif, komunikatif, dan adaptif terhadap audiens modern. Temuan menunjukkan bahwa poster tetap relevan di era digital, asalkan didesain secara strategis untuk meningkatkan daya tarik visual dan efektivitas pesan. Studi ini berkontribusi pada pemahaman lebih luas tentang poster sebagai media penyampaian informasi lintas bidang. Kata Kunci: komunikasi visual, media poster, penyampaian informasi